Ports and Terminals - Ligteringen, Han (TU Delft Open, 2022)
By nature port planning is a multidisciplinary activity. It involves expertise in the field of transport economics, shipping, nautical matters, safety and logistics. But also knowledge of waves and currents, sediment transport and coastal morphology, dredging and land reclamation, and design of breakwaters and quays. Hence port planning is teamwork. But within this team the port planner plays a central role in developing the concepts and obtaining the required expertise at the right time. Most port planners are civil engineers with hydraulic engineering training and experience. The first part of this book (Chapter 1 through 6) is aimed at providing the basic elements to perform this planning process. In Chapter 7 the detailed planning of container terminals is treated, including the logistic process. Further attention is paid to design aspects, typical for such terminals. The objective is to provide the basis for an all-round port engineer, somebody who can participate in the design of any given type of port or terminal. Chapters 8-14 present the planning aspects of other types of terminals.